Peace language and conflict resolution in harmony communication - Fajar Dwi Putra; Sebastian Smolek (International Journal of Communication and Society, 2020)
This study aims to provide an overview of language and conflict resolution to achieve communication harmony. Certain types of description was used to obtain the data more apparently because of related to phenomena and analysis of cases in the community. The conclusions of this study are communication harmony consists of language and communication. Communication becomes very important in giving a touch of the peace symbol. Communities must join together, deliberately creating collective space, starting with oneself, family, and the lowest social level. Although the harmony of communication has not yet materialized, we need to give the maximum extra gratitude for the language of peace from ourselves to the highest level.